Art and Tecnhology. Beyond the normative body - Rico Cuesta, Marta; Durán Domínguez, Guadalupe (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Throughout history, art has always been linked to the body, as a tool and language, an object of representation, support and concept. It becomes a place, border and field for reflection. An element in constant evolution, marked and transformed by social changes. Technology, it has also changed the way we relate to and understand our own body, its political identity, genetic evolution, sexuality, the post-human, transhuman, etc. as a search for new conditions that are emphasized within art in new critical and aesthetic actions that confront these notions of non-normative bodies.